Pengaruh Perilaku Konsumen, Citra Merek dan Influencer terhadap Keputusan Pembelian Shopee di Batam - Sitanggang, Elprida Sari; ., Hikmah (Jurnal Disrupsi Bisnis, 2024)
This study aims to explore the influence of consumer behavior, brand image and influencers on Shopee purchasing decisions in Batam. The population in this study are individuals who use or buy Maybelline brand face powder through Shopee which is not known for certain. To determine the sample, the Jacob Cohen formula was used which resulted in 204 respondents selected using purposive sampling. The data collected for this research was obtained through distributing questionnaires. The data analysis method applied is multiple linear regression. Next, the data is tested through quality tests, classical assumption tests, influence tests and hypothesis tests. The results of the t test show that consumer behavior has a partially positive and significant effect on purchasing decisions. Brand image has a partially positive and significant effect on purchasing decisions. Influencers have a partial positive and significant influence on purchasing decisions. The results of the F test found that consumer behavior, brand image and influencers simultaneously have a positive and significant effect on purchasing decisions.